THE INFLUENCE OF SOCIAL CAPITAL ON THE RESILIENCE OF SASIRANGAN CRAFTSMEN IN BANJARMASIN CITY - Mahmudah Hasanah; Maulana Rizky; Syaripudin Bahar; Alya Pebriana; Kesiya Teresa D.B.P; Zulfa Achira (RADJA PUBLIKA, 2025)
This study aims to examine the influence of social capital on the business resilience of Sasirangan artisans in Banjarmasin City. The research is motivated by an identified research gap, namely the limited empirical studies on the role of social capital in culture-based micro, small, and medium enterprises (MSMEs). Most previous studies have focused on large corporations or formal sectors, while traditional MSMEs such as Sasirangan remain underexplored. Using a quantitative approach with a causal explanatory design, this study involved 21 artisan respondents and analyzed the data through the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The findings reveal that social capital, which consists of norms, networks, and trust, has a significant contribution to business resilience with an R² value of 0.873. This indicates that 87.3% of the variation in business resilience can be explained by the strength of social capital. Theoretically, these findings emphasize the importance of social capital as a non-financial factor in shaping MSME resilience models. Practically, strengthening community norms, expanding networks, fostering trust, and integrating digitalization are key strategies to reinforce artisans’ resilience. The novelty of this study lies in its empirical evidence that social capital is not merely a supporting factor but a key determinant of business sustainability in creative, culture-based industries.